Adherence to Biobehavioral Recommendations in Pediatric Migraine as Measured by Electronic Monitoring: The Adherence in Migraine (AIM) Study. Issue 7 (11th May 2016) - Kroon Van Diest, Ashley M.; Ramsey, Rachelle; Aylward, Brandon; Kroner, John W.; Sullivan, Stephanie M.; Nause, Katie; Allen, Janelle R.; Chamberlin, Leigh A.; Slater, Shalonda; Hommel, Kevin; LeCates, Susan L.; Kabbouche, Marielle A.; et al.
Abstract : Objective: The purpose of this investigation was to examine treatment adherence to medication and lifestyle recommendations among pediatric migraine patients using electronic monitoring systems. Background: Nonadherence to medical treatment is a significant public health concern, and can result in poorer treatment outcomes, decreased cost‐effectiveness of medical care, and increased morbidity. No studies have systematically examined adherence to medication and lifestyle recommendations in adolescents with migraine outside of a clinical trial. Methods: Participants included 56 adolescents ages 11‐17 who were presenting for clinical care. All were diagnosed with migraine with or without aura or chronic migraine and had at least 4 headache days per month. Medication adherence was objectively measured using electronic monitoring systems (Medication Event Monitoring Systems technology) and daily, prospective self‐report via personal electronic devices. Adherence to lifestyle recommendations of regular exercise, eating, and fluid intake were also assessed using daily self‐report on personal electronic devices. Results: Electronic monitoring indicates that adolescents adhere to their medication 75% of the time, which was significantly higher than self‐reported rates of medication adherence (64%). Use of electronic monitoring of medication detected rates of adherence that were significantly higher for participants taking once daily medication (85%) versus participants taking twice daily medication (59%). Average reported adherence to lifestyle recommendations of consistent noncaffeinated fluid intake (M = 5 cups per day) was below recommended levels of a minimum of 8 cups per day. Participants on average also reported skipping 1 meal per week despite recommendations of consistently eating three meals per day. Conclusions: Results suggest that intervention focused on adherence to preventive treatments (such as medication) and lifestyle recommendations may provide more optimal outcomes for children and adolescents with migraine and their families. Once daily dosing of medication may be preferred to twice daily medication for increased medication adherence among children and adolescents.